Production of compost from organic materials and agro waste - Samsu Baharuddin, Azhari; Abu Hassan, Norhasmillah; Muhamad, Zambahari; Sulaiman, Alawi; Dzulkornain, Chairil Anuar; Mokhtar, Mohd Noriznan; Yahya, Azmi (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2014)
Collaboration between Universiti Putra Malaysia (UPM), Universiti Teknologi MARA (UiTM) and Highbiz Trading Sdn. Bhd. was established to transfer knowledge related to composting of organic materials and agro waste. The programme was conducted in Bagan Datoh, Perak community. Feedstock assessment showed that agro waste namely coir dust, poultry manure, oil palm fibre and risk husk are potential feedstock to be utilized into value added product. Oil palm fibre and poultry manure were chosen for the project. These materials were mixed with 1:1 ratio. From 20 t of mixed feedstock produced 10 t of compost. Based on the production of compost, the knowledge related to composting has been successfully transferred to the community. If the system expands to 2,100 t/yr of compost produced in future, a preliminary economic analysis showed that with selling price of RM600/t, the payback period will be 2.83 years and internal rate of return (IRR) will be 7%. However, it is found that this project has problems and limitation such as location of the compost site, social acceptance, travelling distance, facilities and supply of feedstock to be overcome in future. In addition, financial assistance is the critical matters that to be looked into before undertake the project. This project has the potential to be commercialized if the problems and limitation has been arranged.